CUSTOMARY CONFLICT AND BANISHMENT ‘KASEPEKANG’ AT BUNGAYA TRADITIONAL VILLAGE, KARANGASEM REGENCY, BALI: IN THE PERPECTIVE OF CULTURAL STUDIES - Windia, I Wayan; Parimartha, I Gde; Putri Astita, Tjok Istri; Drama Putra, Nyoman (E-Journal of Cultural Studies; Vol. 3, No. 1 Januari 2009, 2012)
-